The Study of Breastfeeding Knowledge among Northern Iranian Teachers - Veghari, G; Mansourian, A (Journal of Nepal Paediatric Society, 2011)
Introduction: Breastfeeding provides all essential nutrients for the first 6 months of life and plays an important role in ensuring health in neonates and mothers. This study was carried out among northern Iranian primary school teachers to determine the knowledge about breastfeeding. Materials and Methods: This is a descriptive-crossectional study and where 745 subjects were chosen by random and cluster sampling. Data was collected by questionnaire about social-demographic and the optimal food awareness at fist 6 months of age. Data was analyzed by SPSS win soft-war. Chi-2 test was used to compare groups. Results: Teacher's knowledge about exclusive breastfeeding and breastfeeding with breast milk substitutes as the best diet was 81.6% and 17.6%, respectively. There was no statistical difference between the teachers who were non-university graduates (78.0%) or those who were university graduates (83.3%). The knowledge of breastfeeding among Turkman and Non-Turkman was 85.1% and 80.2% and male to female was 80.6% and 82.6%, respectively. There were no statistical differences between these variables. Conclusion: The teacher's knowledge about advantages of breastfeeding was low and that it was influenced by social-economic factors. Further studies need to be carried out in this area for determining the difficulties of breastfeeding. Key words: Breastfeeding; Teacher; Knowledge; Ethnicity; Iran DOI: 10.3126/jnps.v31i1.3411 J Nep Paedtr Soc 2010;31(1):39-43